2020
DOI: 10.3126/qjmss.v2i1.29012
|View full text |Cite
|
Sign up to set email alerts
|

Status of Corporate Social Responsibility Practices in Nepal

Abstract: Background: Although there has been a significant interest in corporate social responsibility (CSR) in recent years, there is lack of adequate studies regarding the status of CSR practices in Nepal. The existing studies generally suffer from the narrow conceptualization of CSR, focus on selected companies or industry sector only and from the relatively small sample size. Objectives: This paper aims to identify the status of CSR practices in the Nepalese context. Methods: This study uses questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Moreover, leading politicians in the area have been charged with various malversation of fund and corruption cases (Gutierez, 2013). Even while the significance of individual efforts varies from country to country, it is abundantly clear that the major roles of the government in promoting CSR include demanding, permitting, collaborating, and encouraging various initiatives (Chapagain, 2019). As such, if the government leaders' visions and goals are toward CSR, then initiatives related to it will be channeled.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, leading politicians in the area have been charged with various malversation of fund and corruption cases (Gutierez, 2013). Even while the significance of individual efforts varies from country to country, it is abundantly clear that the major roles of the government in promoting CSR include demanding, permitting, collaborating, and encouraging various initiatives (Chapagain, 2019). As such, if the government leaders' visions and goals are toward CSR, then initiatives related to it will be channeled.…”
Section: Resultsmentioning
confidence: 99%
“…The structured questionnaire consisted of seven constructs having five items under each construct on a five-point Likert scale. The validity of the data collection instrument was ensured through an extensive review of relevant theoretical and empirical literature in the global context (Andrews, 1952; Carr, 1968; Carroll, 1979, 1991; Davenport, 2000; Elkington, 1997; Fernández-Gámez et al , 2019; Freeman, 1984; Friedman, 1970; Koch, 1979; Matten and Crane, 2005; Porter and Kramer, 2006, 2011; Scherer and Palazzo, 2011; Scherer et al , 2016; Tortosa-Edo and López-Navarro, 2021) as well as in the Nepalese context (Chapagain, 2020; Sthapit, 2021) while preparing the instrument. For instance, the five items for CSR vis-à-vis corporate philanthropy have been adopted from Carroll (1991) and the items for CSV approach have been derived from Porter and Kramer (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies regarding the managers’ attitudes and views on CSR have been conducted in the Nepalese context as well. Chapagain (2008) found that the views of managers of the Nepalese banking sector on CSR were mainly guided by moral perspectives rather than strategic ones. Likewise, Adhikari et al (2016) have reported that the CSR perspectives of Nepalese executives and opinion leaders closely resembled with economic responsibilities of business.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In developing nations like Nepal, CSR may play an important role in the socioeconomic development of the society (NRB, 2021). In Nepal, big corporations have much greater levels of CSR practices than do small and medium-sized businesses (Chapagain, 2020). Bista (2017) observed that although there is awareness about CSR activities of commercial banks, its trend is unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…They are also found serving people who are suffering from natural calamities and disasters (Khanal, 2019). Nepalese businesses are still not paying adequate attention on social and environmental issues (Chapagain, 2020). However, the majority of banking and financial firms engage in CSR activities to improve their reputation (NRB, 2021).…”
Section: Introductionmentioning
confidence: 99%